Generalized Newton–Cartan geometries for particles and strings. (13th March 2023) - Bergshoeff, E A; van Helden, K; Lahnsteiner, J; Romano, L; Rosseel, J
Abstract: We discuss the generalized Newton–Cartan geometries that can serve as gravitational background fields for particles and strings. In order to enable us to define affine connections that are invariant under all the symmetries of the structure group, we describe torsionful geometries with independent torsion tensors. A characteristic feature of the non-Lorentzian geometries we consider is that some of the torsion tensors are so-called 'intrinsic torsion' tensors. Setting some components of these intrinsic torsion tensors to zero leads to constraints on the geometry. For both particles and strings, we discuss various such constraints that can be imposed consistently with the structure group symmetries. In this way, we reproduce several results in the literature.